2014
DOI: 10.1111/are.12653
|View full text |Cite
|
Sign up to set email alerts
|

Feeding increasing levels of corn gluten meal induces suboptimal muscle pigmentation of rainbow trout (Oncorhynchus mykiss)

Abstract: A 24‐week growth trial was conducted to evaluate the effects of feeding levels of corn gluten meal (CGM) on growth performance and pigment deposition in the muscle of rainbow trout (Oncorhynchus mykiss). Three isonitrogenous and isoenergetic (digestible energy basis) experimental diets were formulated to contain increasing levels of CGM (0%, 9% and 18%) and 50 mg kg−1 of astaxanthin. Each diet was fed in triplicate to groups of 75 fish (initial average body weight = 549 g fish−1) reared at 8.5°C. The inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
3
11
0
2
Order By: Relevance
“…Fish fillet colour is affected by coloured feed ingredient like corn gluten which contains lutein and yellow carotenoid pigments. This was shown in studies on salmon and trout (Buttle et al, 2001;Saez et al, 2016). CPC used in our study has more pigment than corn gluten which causes slight change in tilapia fillet.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Fish fillet colour is affected by coloured feed ingredient like corn gluten which contains lutein and yellow carotenoid pigments. This was shown in studies on salmon and trout (Buttle et al, 2001;Saez et al, 2016). CPC used in our study has more pigment than corn gluten which causes slight change in tilapia fillet.…”
Section: Discussionsupporting
confidence: 72%
“…It has been shown that replacing fish meal with plant protein causes several effects on fish growth and body composition, histological and morphological changes in the digestive system which affect digestion (Caballero, Izquierdo, Kjorsvik, Fernandez, & Rosenlund, ; Green & McCornick, ; Hall & Bellwood, ; Jalili, Tukmechi, Agh, Noori, & Ghasemi, ; Krogdahl & Bakke, ), intestinal microbial community (Llewellyn, Boutin, Hoseinifar, & Derome, ; Merrifield & Rodiles, ; Ringø, Dimitroglou, Hoseinifar, & Davies, ) and fillet colour (Buttle, Crampton, & Williams, ; Saez, Abdel‐Aal, & Bureau, ). Therefore, in order to evaluate CPC properly, it is important to consider studying all the above‐mentioned parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Studies assessing the effect of dietary astaxanthin on the skin and flesh pigmentation of aquatic animals are summarized in Table 7. In fact, a great deal of in-depth study has investigated the effective use of dietary astaxanthin in finfish feeds being responsible for the skin and muscle pigmentation of rainbow trout O. mykiss (Torrissen 1989;Storebakken & Choubert 1991;Sommer et al 1992;Choubert et al 1994;Nickell & Bromage 1998;Choubert et al 2006;Ingle de la Mora et al 2006;Page & Davies 2006;Ytrestoyl & Bjerkeng 2007a;Choubert et al 2009;Choubert 2010;Saez et al 2014), red porgy P. pagrus (Chatzifotis et al 2005;Kalinowski et al 2005;Tejera et al 2007;Chatzifotis et al 2011), gilthead sea bream Sparus aurata (Gomes et al 2002), red sea bream P. major (Katayama et al 1965;Tanaka et al 1976;Ibrahim et al 1984;Nakazoe et al 1984;Lin et al 1998), olive flounder Paralichthys olivaceus (Pham et al 2014), Atlantic salmon S. salar Wathne et al 1998;Bjerkeng & Berge 2000;Buttle et al 2001;Baker et al 2002;Page & Davies 2006;Ytrestoyl & Bjerkeng 2007b;Chimsung et al 2013), Australasian snapper Pagrus auratus (Booth et al 2004;Doolan et al 2008a,b), channel catfish Ictalurus punctatus ) and yellow croaker Larimichthys croceus Yi et al 2014). Numerous previous investigations reported significant astaxanthin deposition in skin and muscle o...…”
Section: Skin and Flesh Pigmentationmentioning
confidence: 99%
“…A major concern in diet formulation for salmonids is the maintenance of red flesh colouration. Astaxanthin is the primary carotenoid responsible for this red colouration and is also a major precursor to vitamin A (Anderson 2001;Saez et al 2016). In previous studies of rainbow trout, diets that included plant protein sources, mainly corn gluten meal, were associated with reduced tissue colouration relative to fishmeal diets (Saez et al 2014(Saez et al , 2016.…”
Section: Introductionmentioning
confidence: 99%
“…Astaxanthin is the primary carotenoid responsible for this red colouration and is also a major precursor to vitamin A (Anderson 2001;Saez et al 2016). In previous studies of rainbow trout, diets that included plant protein sources, mainly corn gluten meal, were associated with reduced tissue colouration relative to fishmeal diets (Saez et al 2014(Saez et al , 2016. This difference may occur because corn gluten meal contains high levels of yellow xanthophylls (lutein and zeaxanthin; 150-500 mg/kg) (Park et al 1997;Moros et al 2002), which do not impart the same red flesh colouration and could limit astaxanthin uptake due to passive interference during digestion (Furr and Clark 1997;Olsen and Baker 2006).…”
Section: Introductionmentioning
confidence: 99%